PENDAMPINGAN PENGGUNAAN KEMASAN “Vacum Sealer” PADA PRODUK OLAHAN IKAN BANDENG DI DESA GERSIK PUTIH KEC. GAPURA SUMENEP - Putri, Rika Diananing; Hanafi, Imam (UNIVERSITAS PGRI MADIUN, 2021)
Abstract. Bandeng is a fish that is in demand by all circles. UKM Adinda (partner) is located in gersik putih village of Gapura Sumenep which has a business made from bandeng. One of the preparations is otak-otak bandeng which is very popular with the public. The purpose of community service is to provide packaging knowledge on processed bandeng, especially otak-otak bandeng so as to provide quality for the product, and can increase the selling value. The method of implementing this service is by socializing, mentoring partners so that they can implement them in their processed products. The results obtained were that the partners were able to design packaging to increase the selling value of otak-otak bandeng products, thereby increasing the partner's income. Conclusion of activities with partners with rapid and attractive packaging, with creative and innovative designs, and in accordance with established standards, which is consistent, creates a form of promotion that is creative, informative, and easy to understand about products marketed by utilizing digital marketing. Abstrak. Bandeng merupakan ikan yang diminati oleh semua kalangan. UKM Adinda (mitra) beralokasi di desa gersik putih Gapura Sumenep yang memiliki usaha olahan berbahan ikan bandeng. Salah satu olahannya otak otak bandeng yang sangat digemari oleh masyarakat. Tujuan pengabdian kepada masyarakat adalah untuk memberikan pengetahuan pengemasan terhadap olahan bandeng khususnya otak otak bandeng sehingga memberikan mutu bagi produk nya, dan dapat meningkatkan nilai jual. Metode pelaksanaan pengabdian ini dengan sosialisasi, pendampingan pada mitra hingga dapat mengimplementasikan pada produk olahannya. Hasil yang diperoleh, mitra mampu mendesain kemasan untuk meningkatkan nilai jual produk otak-otak bandeng sehingga meningkatkan pendapatan mitra. Kesimpulan kegiatan bersama mitra dengan kemasan rapid an menarik, dengan desain kreatif dan inovatif, dan sesuai denga standar yang ditetapkan, yang konsisten, menciptakan bentuk promosi yang kreatif, informative, dan mudah dipahami tentang produk yang dipasarkan dengan memanfaatkan digital marketing.